Prenatal antidepressant exposure and behavioral problems in early childhood – a cohort study. (5th November 2012) - Pedersen, L. H.; Henriksen, T. B.; Bech, B. H.; Licht, R. W.; Kjaer, D.; Olsen, J.
<x xml:space="preserve">Abstract</x> Objective To estimate a potential association between in utero exposure to antidepressants and behavioral problems in childhood. Method Information on exposures was obtained from the Danish National Birth Cohort. We studied the children of 127 mothers who had used antidepressants during pregnancy and compared these to 98 children of mothers with a prenatal depression with no use of antidepressants during pregnancy and 723 children of mothers with no prenatal depression and no use of antidepressant during pregnancy (unexposed). Behavioral problems were assessed at 4 or 5 years of age by the parent‐reported Strengths and Difficulties Questionnaire (SDQ). Results Prenatal antidepressant exposure was not associated with abnormal SDQ scores compared with prenatal exposure to untreated prenatal depression or to no exposure. Untreated prenatal depression was associated with abnormal SDQ scores in the subscales of conduct [adjusted odds ratio (aOR) 2.3 (95% CI, 1.2–4.5)] and prosocial problems [aOR 3.0 (95% CI, 1.2–7.8)] compared with unexposed children. Total SDQ score was higher in children of mothers with untreated prenatal depression. These associations attenuated after adjusting for postnatal maternal psychiatric disease. Conclusion Prenatal antidepressant exposure was not associated with behavioral or emotional problems in early childhood.